Merauke “Food Estate”: Alternatif Penanganan Konflik di Papua dalam Perspektif Ekonomi-Sosial dan Budaya - Binsar Sianipar; Amanah Nurish (Intermestic: Journal of International Studies, 2021)
This study analyzes food estate in Merauke as a conflict resolution alternative in Papua from economic-social and cultural perspectives. The conflicts in Papua are still happening and no best solution has been found yet. Among the roots of the problem are economic and social disparities as well as cultural disharmony. The government is planning to develop a food estate in Merauke, Papua to enhance national food security and as export commodities. Apart from the Government’s objectives, the analysis used qualitative research methods with a sociological approach through field observation and participation. Adopting Galtung’s theory of violence, it shows the food estate in Merauke can potentially contribute to resolving conflicts in Papua, especially to eliminate direct violence and structural violence